Relationship of Demographic Profile to Satisfaction in Interprofessional Collaboration among Medical-Surgical Ward Nurses in Selected Hospitals of Shandong, China: A Cross-Sectional Study - Li, Meng; Agunod, Cyrelle D. (International Journal of Public Health and Medical Research, 2024)
With the spread of the concept of team medicine, active nurse-doctor collaboration is closely related to nursing quality. Nursing standards recognize that collaborative practice is a necessary condition for high-quality patient care, but many nurses are often reluctant to participate in interprofessional teams, indicating that challenges in nurse-doctor collaboration still exist. This study aimed to investigate the relationship between demographic data and nurse interprofessional satisfaction of medical and surgical nurses in tertiary hospitals in Shandong Province, and to provide a reference direction for improving teamwork. Methods: The research method was a cross-sectional study. Medical and surgical nurses in three tertiary hospitals in Shandong Province were surveyed. Medical and surgical nurses who were officially registered in the hospital and had been engaged in internal medicine or surgery for at least one year were selected. They were aged 18 to 45 years. The researchers used SPSS software to analyze the data, and descriptive statistics (frequency percentage distribution, mean score, and standard deviation) were used to present the satisfaction scores. If the data did not follow a normal distribution, nonparametric tests were used. Results: The average scores of the interprofessional collaboration satisfaction scale for the participating nurses were: "overall expectation" 2.67; "perception dimension of professional collaboration" 3.78; "The overall relationship satisfaction of professional cooperation" 3.83; "Communication and tolerance of interprofessional collaboration" 3.80; "Equality of interprofessional collaboration" 3.81; "Satisfaction with interprofessional collaboration" 2.98. The results of non-parametric tests showed that there was a significant difference between marriage and nurses’ satisfaction with interprofessional collaboration (P<0.05). Conclusion: The overall satisfaction of nurses with interprofessional collaboration in three tertiary hospitals in Shandong Province was generally average. The three hospitals should improve the management model and care about the mental health of nurses according to factors such as the marital status of nurses. Nurses should make a good distinction and plan between work and life to promote interprofessional collaboration.